Differences in Cognitive-Perceptual Factors Arising From Variations in Self-Professed Paranormal Ability - Drinkwater, Kenneth Graham; Dagnall, Neil; Denovan, Andrew; Williams, Christopher (Frontiers in Psychology, 2021)
This study examined whether scores on indices related to subclinical delusion formation and thinking style varied as a function of self-professed paranormal ability. Specifically, compared to individuals with self-professed ability and no ability, paranormal practitioners (i.e., Mediums, Psychics, Spiritualists, and Fortune-Tellers) were expected to score higher on paranormal belief, proneness to reality testing, and emotion-based reasoning, and lower on belief in science. Similar differences were predicted between the self-professed and no ability conditions. A sample of 917 respondents (329 males, 588 females) completed self-report measures online. Multivariate analysis of variance (MANOVA), supported hypotheses for belief in the paranormal, proneness to reality testing deficits, and emotion-based reasoning. However, belief in science scores were only lower for the practising vs. no ability, and the ability vs. no ability comparisons (the practicing vs. ability groups did not differ). Results were consistent with previous studies of paranormal belief and experience, which report that paranormal-related cognitions and perceptions are characterised by specific psychological characteristics. Explicitly, variables related to subclinical delusion formation and emotion-based/intuitive thinking.